Creation of a biosample collection from patients after myocardial infarction in the Khanty Mansi Autonomous Okrug — Yugra - A V Morozkina; A S Vorobev; M Yu Donnikov; L V Kovalenko; M L Safronova; A Kh Gapurova; K Yu Nikolaev (Кардиоваскулярная терапия и профилактика)
Aim. Creation of a sample collection of whole blood, leukocyte suspension, genomic deoxyribonucleic acid from patients with myocardial infarction for fundamental and applied research in medicine.Materials and methods. The collection, transportation and processing of biomaterial samples in the biobank of the Medical Institute of Surgut State University were carried out according to standard methods using recommendations, standard operating procedures and national guidelines for biobanking.Results. As of September 1, 2023, the collection has collected 744 aliquots of whole blood and leukocyte suspension and isolated 108 samples of genomic deoxyribonucleic acid from 108 donors after myocardial infarction. Aliquots of samples from the biobank collection are actively used for a number of molecular genetic studies (genotyping, massively parallel sequencing).Conclusion. This biosample collection on the basis of Surgut State University provides current and future research projects in cardiology with high-quality biomaterial.